Cerebrospinal Fluid Learning Exercise - Holly Ressetar; Edwin Allen (Association of American Medical Colleges, 2011)
Abstract The cerebrospinal fluid (CSF) learning exercise demonstrates the concepts of CSF production, circulation and absorption as well as introduce the student to the pathogenesis of hydrocephalus. The animated module is designed to facilitate medical, dental, and paramedical student visualization of CSF circulation and function. The exercise is presented in a stepwise fashion, starting with stated learning objectives and concluding with self-test exercises. Students navigate through a series of animated images accompanied by descriptive text. Self-test exercises promote interactivity and provide students with immediate feedback. The module may be used as an independent informational unit suitable for learners with some background in brain anatomy or may be used for medical board review. This module has been implemented in first-year medical and first-year pharmacy courses that integrate gross anatomy and histology. Informal student feedback is positive and reports that the animations facilitate student understanding of the material. Students also report that the module is easy to navigate and is very clear in its objectives. The module has not yet been formally evaluated for its effectiveness in improving student performance on exam questions.